Research on the Low-cycle Structural Strength of the Fuel Tank Membrane. (2017) - Skvortsov, Yu. V.; Glushkov, S.V.; Aistov, A.I.
Abstract: A spherical fuel tank with internal space divided into a fuel chamber and a gas chamber by a thin metal membrane is under analysis. When excessive pressure is applied to the gas chamber, the membrane expels the gas under the strain. The goal of the research is to evaluate the working order of the membrane based on low-cycle strength criteria. Its stress-strain state calculations are done with the finite elements method using the ANSYS® programme in view of the geometrical and physical nonlinearity, and contact interaction with the walls of the fuel tank. Durability evaluation is performed based on FEM calculation results. Calculated durability values correlate accurately with the performed experiments.